An optimization model for course scheduling in Undergraduate Industrial Engineering Program of Universitas Sebelas Maret. Issue 1 (February 2021) - Pratiwi, M; Rosyidi, C N; Yuniaristanto,
Abstract: Course timetabling is a common problem in many universities. With different number of students enrolled in every course, the number of lecturers, and various size of room's capacity, then it would be difficult for scheduler to assign courses manually. The assigning process must meet all of educational rules in order to satisfy students and lecturers for a better educational quality. There are sets of time slot, courses, and rooms. The room efficiency and the effectiveness needed due to limited available room. The problem is formulated in the form of binary integer linear programming. The objective function of the model is to maximise the room utility. The model also considers probability of a course taken by different student groups in order to avoid clash. The results show a significant difference between manual scheduling and optimization results can satifsy more constraints than manual scheduling.